BIVALIRUDIN AND PERCUTANEOUS CORONARY INTERVENTIONS IN PATIENTS WITH ACUTE CORONARY SYNDROME: THEORY AND PRACTICE - O. V. Averkov (Российский кардиологический журнал)
This analytical paper presents the key information on the mechanism of action of a direct thrombin inhibitor – bivalirudin. The difference between bivalirudin and unfractionated or low molecular weight heparins, as well as fondaparinux, in terms of the mechanism of action, pharmacokinetics, and pharmacodynamics, is discussed. The results of clinical trials of bivalirudin and the position of this medication in the current clinical guidelines on acute coronary syndrome treatment are summarized. A detailed description of bivalirudin dosage is presented, together with the recommendations on its effective and safe use in clinical practice.